Can the Celebrity Speak? Controversies and the Eulogistic Fandom of Shah Rukh Khan. (July 2022) - Misra, Abir
This article addresses the participation of celebrities and their fans in media controversies. As techno-social events, controversies are constitutive of discursive battles, between numerically conscious participatory communities, aimed at describing the meaning and significance of cultural symbols. Celebrities, in their capacity as cultural symbols, provide the ground for staging these discursive battles. Fan participation, as auxiliary of celebrity participation, is studied here specifically to discern its essential functions vis-a-vis controversies. For elaborating its argument, this article looks at Shah Rukh Khan (hereafter SRK) and his fandom in India. SRK, as a transcultural symbol of Liberal Islam, was embroiled in media controversies wherein the meaning and significance of his 'Muslimness' was debated and scrutinised. Marked by struggles between SRK fandom, on one side, and right-wing/reactionary groups on the other, these controversies testify SRK's centrality in political debates surrounding the 'Muslim Question' in Indian Polity. This article argues that SRK Fandom's primary discursive function is to create an 'Eulogistic Buffer' that insulates SRK from right-wing/reactionary islamophobia.